The Effect of Of Box Jump, Double Leg Speed Hops Training and Ankle-Knuckles Coordination Against the Results of Shots on Goal of the Soccer Players at SMPN 27 Padang - Syahrastani Syahrastani; M. Ereizky Dwi Fadillah .S. (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
Soccer is one of the very popular sports that is enjoyed by all ages and levels of society. Soccer players must know about the basic techniques, one of which is kicking the ball. Success in kicking the ball requires training for leg muscle power. Plyometric exercises (such as box jumps, and double leg speed hops) can be used to train leg muscle power. The purpose of the study was to determine the effect of box jump exercise, double leg speed hops and ankle-knuckles coordination against the results of shots on goal of the soccer players from SMPN 27 Padang. This research is an experimental study with a 2x2 factorial design. The population of the study was soccer players at SMPN 27 Padang totaling 32 people. Data analysis used 2x2 ANOVA and Tukey's further test at a significance level of = 0.05. The results showed that soccer players at SMPN 27 Padang who had high ankle-knuckles coordination had better shots on goal when trained with Box Jump exercises. Meanwhile, those who have low ankle-knuckles coordination have better shots on goal if they are trained with the Double Leg Speed ​​Hops exercise. There is an interaction between training methods and ankle-knuckles coordination against the results of shots on goal of the soccer players at SMPN 27 Padang.